Government Policy and Islamic Education Quality Advancement in Indonesia - Imam Musthofa; Helmiati Helmiati; Hariza Hasyim (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study analyzes Indonesian government policies on improving national education quality and their implications for the advancement of Islamic education. Over the past two decades, education quality has become a central issue in the national education system, particularly following the implementation of the National Education Standards, the Education Quality Assurance System, teacher certification, the Teacher Professional Education program, and the Merdeka Belajar–Kampus Merdeka initiative. Employing a descriptive qualitative method with a library research approach, this study examines regulatory documents, ministry reports, books, and scholarly articles published between 2019 and 2025. The findings indicate that government policies have significantly strengthened Islamic education in both public schools and madrasahs. Curriculum reform, teacher professional development, and madrasah digitalization are identified as key drivers of progress. Nonetheless, challenges persist, including regional disparities in quality, limited human resources, and uneven institutional capacities. Therefore, synergy between the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs is essential to establish an integrated quality assurance system that aligns with Islamic values and supports sustainable educational advancement.